1996
DOI: 10.1038/sc.1996.100
|View full text |Cite
|
Sign up to set email alerts
|

The inter rater reliability of the original and of the modified Ashworth scale for the assessment of spasticity in patients with spinal cord injury

Abstract: Thirty patients with spinal cord injury (SCI) were randomly selected to participate in this study which evaluated the inter rater reliability of the original and of the modified Ashworth scale for the assessment of spasticity in the lower limbs. A doctor and a physiotherapist rated the muscle tone of hip adductors, hip extensors, hip flexors and ankle plantarflexors according to the original and to the modified Ashworth scale. The results were analyzed using a Cohen's Kappa statistical test and showed varying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
102
1
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(110 citation statements)
references
References 15 publications
5
102
1
2
Order By: Relevance
“…Although this is an unconventional means of administering the MAS, this methodology allowed us to ensure a consistent velocity for assessment across subjects and raters as it was impractical to apply the velocity constraint on the first cycle. Despite this standardization of the measurement procedure, our results are similar to Haas et al 19 who compared the test-retest reliability of the Ashworth and MAS among subjects with SCI and lower extremity spasticity. In Haas' study, 19 the need to establish a standardized speed of muscle stretching during the test was identified.…”
Section: Muscle Groupsupporting
confidence: 89%
See 3 more Smart Citations
“…Although this is an unconventional means of administering the MAS, this methodology allowed us to ensure a consistent velocity for assessment across subjects and raters as it was impractical to apply the velocity constraint on the first cycle. Despite this standardization of the measurement procedure, our results are similar to Haas et al 19 who compared the test-retest reliability of the Ashworth and MAS among subjects with SCI and lower extremity spasticity. In Haas' study, 19 the need to establish a standardized speed of muscle stretching during the test was identified.…”
Section: Muscle Groupsupporting
confidence: 89%
“…Despite this standardization of the measurement procedure, our results are similar to Haas et al 19 who compared the test-retest reliability of the Ashworth and MAS among subjects with SCI and lower extremity spasticity. In Haas' study, 19 the need to establish a standardized speed of muscle stretching during the test was identified. In addition, they identified that the effects of rater training was not well evaluated.…”
Section: Muscle Groupsupporting
confidence: 89%
See 2 more Smart Citations
“…14,22 While the Ashworth and modified Ashworth scales 14,15,23 are commonly used to assess the severity of spasticity, there is some question about their validity in the lower limbs of persons with SCI. 24 As spasticity outcomes vary between clinical patient groups and depend on a variety of factors within each individual, a battery of assessment tools is recommended, incorporating clinical, electrophysiologic, neurophysiological, 25 and/or biomechanical techniques. 14,26,27 It is important to note that there are generally poor correlations among clinical scales and, further, reductions in spasticity are not necessarily correlated with improvement in function.…”
Section: Introductionmentioning
confidence: 99%